Community structure and diversity of polychaetes (Annelida) in the deep Weddell Sea (Southern Ocean) and adjacent basins - Schüller, Myriam; Ebbe, Brigitte; Wägele, J.-Wolfgang (2009)
Abstract Introduction Material and methods Results Efficiency and suitability of sampling gear Composition of polychaete samples Sample-size independent diversity and similarity measures Sample-size dependent diversity and similarity measures Discussion Conclusion References